2006
DOI: 10.3310/hta10170
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trials of conventional antipsychotic versus new atypical drugs, and new atypical drugs versus clozapine, in people with schizophrenia responding poorly to, or intolerant of, current drug treatment

Abstract: Non-UK purchasers will have to pay a small fee for post and packing. For European countries the cost is £2 per monograph and for the rest of the world £3 per monograph.You can order HTA monographs from our Despatch Agents:-fax (with credit card or official purchase order) -post (with credit card or official purchase order or cheque) -phone during office hours (credit card only).Additionally the HTA website allows you either to pay securely by credit card or to print out your order and then post or fax it. NHS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(65 citation statements)
references
References 121 publications
(186 reference statements)
1
62
0
2
Order By: Relevance
“…Our findings are in agreement with that study regarding the extra-pyramidal side effects of flupenthixol decanoate , but practically poles apart concerning efficacy. The positive effect of combining flupenthixol decanoate with aripiprazole in our experiment slightly supports the argument of some earlier studies regarding the advantages of FGAs versus SGAs [7]. Essentially, long-acting depot injections of drugs such as flupenthixol decanoate are extensively used as a means of long-term maintenance treatment for schizophrenia, and according to a study there is no difference between flupenthixol decanoate and other depot antipsychotics regarding management of schizophrenia, especially when its prevention of relapse in standard dose is not different from higher dose [16].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings are in agreement with that study regarding the extra-pyramidal side effects of flupenthixol decanoate , but practically poles apart concerning efficacy. The positive effect of combining flupenthixol decanoate with aripiprazole in our experiment slightly supports the argument of some earlier studies regarding the advantages of FGAs versus SGAs [7]. Essentially, long-acting depot injections of drugs such as flupenthixol decanoate are extensively used as a means of long-term maintenance treatment for schizophrenia, and according to a study there is no difference between flupenthixol decanoate and other depot antipsychotics regarding management of schizophrenia, especially when its prevention of relapse in standard dose is not different from higher dose [16].…”
Section: Discussionsupporting
confidence: 92%
“…However, these claims have not been consistently confirmed by empirical data; so, researchers and clinicians differ in their attitudes concerning the comparative effectiveness of FGAs and SGAs [4,5]. Despite the lack of consensus, atypical antipsychotic drugs have become the most commonly used class of antipsychotic drugs in clinical practice [6][7][8]. However, according to one study, conventional drugs were associated with nonsignificantly better outcomes and lower costs in comparison with atypical drugs [9].…”
Section: Introductionmentioning
confidence: 99%
“…FGAs, which are substantially cheaper, still have a place in the treatment of patients unresponsive or intolerant to the newer medications. 33 In addition, another report has noted that there is no clear evidence that SGAs are more effective or better tolerated than FGAs. 34 Those authors concluded that FGAs should be used in the initial treatment of an episode of schizophrenia, unless the patient has not previously responded to these drugs or has unacceptable extrapyramidal side effects.…”
Section: Resultsmentioning
confidence: 99%
“…Within the sample, a number of instruments (25 of 54) were considered piloted, although as observed in our previous review [1], authors used a variety of methods ranging from direct application of an annotated system [5,17], inclusion in specifically designed pilot programs [18], and reliance on previously used questionnaires from similar [19] and dissimilar [15] studies. Because of the importance of pilot testing, it would be necessary to include details of the methods employed within the database.…”
Section: Pilot Testingmentioning
confidence: 99%